Landscape's Revenge : The Ecology of Failure in Robert Walser and Bernardo Carvalho. - Yurgel, Caio. (Latin American Literatures in the World / Literaturas Latinoamericanas en el Mundo Series, 2018)
The book series "Latin American Literatures of the World" presents an innovative understanding of literatures written in Latin America and the Caribbean. Informed by current perspectives on world literary studies and cultural theory, it focuses on works that deal with the multiple global connections of Latin American literatures. This comprises determined aesthetics and forms of writing, as well as book-market-related phenomena.